Image of Kubera accompanied by his vahana - Temples of India Project Team (Jio Institute, 2024)
Kubera, the God of wealth, is depicted as four-armed, accompanied by his vahana (mount), the elephant. Crowned and bejewelled, Kubera holds a money bag in his upper hand, a gada (mace) in his lower right hand and a kamandalu (water pot) in his lower left hand.